Immune escape variants of H9N2 influenza viruses containing deletions at the hemagglutinin receptor binding site retain fitness in vivo and display enhanced zoonotic characteristics - Peacock, TP; Benton, DJ; James, J; Sadeyen, J-R; Chang, P; Sealy, JE; Bryant, JE; Martin, SR; Shelton, H; Barclay, WS; Iqbal, M (American Society for Microbiology, 2017)
H9N2 avian influenza viruses are enzootic in poultry across Asia and North Africa, where they pose a threat to human health as both zoonotic agents and potential pandemic candidates. Poultry vaccination against H9N2 viruses has been employed in many regions; however, vaccine effectiveness is frequently compromised due to antigenic drift arising from amino acid substitutions in the major influenza virus antigen hemagglutinin (HA). Using selection with HA-specific monoclonal antibodies, we previously identified H9N2 antibody escape mutants that contained deletions of amino acids in the 220 loop of the HA receptor binding sites (RBSs). Here we analyzed the impact of these deletions on virus zoonotic infection characteristics and fitness. We demonstrated that mutant viruses with RBS deletions are able to escape polyclonal antiserum binding and are able to infect and be transmitted between chickens. We showed that the deletion mutants have increased binding to human-like receptors and greater replication in primary human airway cells; however, the mutant HAs also displayed reduced pH and thermal stability. In summary, we infer that variant influenza viruses with deletions in the 220 loop could arise in the field due to immune selection pressure; however, due to reduced HA stability, we conclude that these viruses are unlikely to be transmitted from human to human by the airborne route, a prerequisite for pandemic emergence. Our findings underscore the complex interplay between antigenic drift and viral fitness for avian influenza viruses as well as the challenges of predicting which viral variants may pose the greatest threats for zoonotic and pandemic emergence. IMPORTANCE: Avian influenza viruses, such as H9N2, cause disease in poultry as well as occasionally infecting humans and are therefore considered viruses with pandemic potential. Many countries have introduced vaccination of poultry to try to control the disease burden; however, influenza viruses are able to rapidly evolve to escape immune pressure in a process known as "antigenic drift." Previously, we experimentally generated antigenic-drift variants in the laboratory, and here, we test our "drifted" viruses to assess their zoonotic infection characteristics and transmissibility in chickens. We found that the drifted viruses were able to infect and be transmitted between chickens and showed increased binding to human-like receptors. However, the drift mutant viruses displayed reduced stability, and we predict that they are unlikely to be transmitted from human to human and cause an influenza pandemic. These results demonstrate the complex relationship between antigenic drift and the potential of avian influenza viruses to infect humans.